The Development of Work Based Learning Kolaboratif (WBL-K) Model to Improve Automotive Maintenance Competence in Community Colleges - Sugiyarto, Sugiyarto (Universitas Negeri Semarang, 2020)
The enactment of the ASEAN Economic Community (AEC) has an impact on free movement of goods, services, capital, investment, and skilled labour entering to Indonesia. This case is a challenge for education in Indonesia to prepare competent human resources. One of the efforts to prepare the competent human resources is through the implementation of the Work Based Learning Kolaboratif (WBL-K) model. The implementation of WBL-K aims to make vocational education have a high level of efficiency and relevance to the industrial needs. The purpose of the study is to develop WBL-K model to improve automotive maintenance competence in community colleges. This study used Research and Development (R&D) method with the 4D development model, which consisted of define, design, develop, and disseminate. The instruments used in this research were (1) the WBL-K model assessment sheet; (2) practicality questionnaire for the WBL-K model; and (3) pre-test and post-test questions. The data analysis used in this study were (1) criteria to determine the feasibility level of WBL-K model; (2) criteria to determine the practicality level of WBL-K model; and (3) N-Gain and N-Gain difference test using the t test to determine the effectiveness of WBL-K model. The results of the feasibility test, practicality test, and effectiveness test of WBL-K model developed show that: (1) based on the responses of model experts and material experts (lecturers and automotive industry instructors), it is obtained that the criteria of the WBL-K model is very feasible; (2) based on the user responses (lecturers, industrial instructors, and students),Ã‚Â it is obtained that the criteria WBL-K model is very practical to use; (3) from the effectiveness test in the experimental group, it is obtained the criteria that the WBL-K model is quite effective and significant to improve the competence of automotive maintenance in community colleges.